2020
DOI: 10.3390/medicina57010011
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disturbances and Related Problems in Italian University Medical Students from 2000 to 2020: An Integrative Review of Qualitative and Quantitative Studies

Abstract: Background and objectives: The presence of mental health problems in the population of medical students in Italy has been evaluated in several cross-sectional studies, which have used different methodologies and study designs. However, a global overview of the prevalence of mental health problems in Italian medical students is not available, although this would be essential for promoting preventive strategies and supportive treatments. Materials and Methods: An integrative review aiming to describe the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Assessment with item #9 of the BDI-II likewise found the presence of suicidal ideation in nearly one in five students. However, our data concurs with that of Sampogna et al (2020) about the percentage of suicidal thoughts in Italian medical students, which was reported to be around 17%. Because our finding agrees with the Italian data but differs from those abroad and in the general population, the evidence adds statistical significance to the psychological condition of medical students in Italy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Assessment with item #9 of the BDI-II likewise found the presence of suicidal ideation in nearly one in five students. However, our data concurs with that of Sampogna et al (2020) about the percentage of suicidal thoughts in Italian medical students, which was reported to be around 17%. Because our finding agrees with the Italian data but differs from those abroad and in the general population, the evidence adds statistical significance to the psychological condition of medical students in Italy.…”
Section: Discussionsupporting
confidence: 92%
“…Among Italian medical students, according to Sampogna et al (2020) , the results showed a high prevalence of substance use, especially alcohol (range 13–86%), cigarettes (range 15–31%,), compared to Italian students from other degree programs. Cigarette use is also slightly higher than in the general population in Italy, which is around 20% ( Lugo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…University years coincide with the peak period of risk for the onset of mental disorders (34), and they are associated with a significant increase in risky health behaviors (35). Considering the importance of undergraduate students to the future social capital of society and the potential negative impact of mental health problems on their lives, prevention and early treatment of mental health problems in these specific years represent a key public health priority (36)(37)(38).…”
Section: Bismentioning
confidence: 99%
“…Along with that, another potential limitation was the absence of medical students in the current study. Medical students are reported being in a higher risk compared to other student majors and the general population in developing depressive disorders ( Rotenstein et al., 2016 ), anxiety disorders and substance abuse ( Sampogna et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%